Implementing slab solar water heating system - Raveendran S.K.; Shen C.Q. (American Institute of Physics Inc., 2023)
Water heating contributes a significant part of energy consumption in typical household. One of the most employed technologies today that helps in reducing the energy consumption of water heating would be conventional solar water heating system. However, this system is expensive and less affordable by most family. The main objective of this project is to design and implement an alternative type of solar water heating system that utilize only passive solar energy which is known as slab solar water heating system. Slab solar water heating system is a system that heat up cold water using the solar radiance from the sun. The unique part of this system is that it does not require any form of electricity in order to operate. Solar radiance is converted into heat energy through convection method and cold water will be heated up by using conduction method [1]. The design of this system is governed by the criteria of low implementation cost and energy saving. Selection of material in the construction of a slab solar water heating system is important as it will directly affect the efficiency and performance of the system. A prototype has been built to realize the idea and it had been proven that this system was able to provide sufficient hot water supply for typical household usage at any given time. 2015 AIP Publishing LLC.